2017
DOI: 10.1515/hukin-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Application of Two Intervention Programs in Order to Optimize Motivation and to Improve Eating Habits in Adult and Elderly Women

Abstract: The objective of this study was to analyse the effectiveness of two intervention programs: a physical exercise program with strategies to support the three basic psychological needs (autonomy, competence and relatedness); and a physical exercise program with nutritional education in order to improve the lifestyles of adult and elderly women who practiced functional maintenance. The Self-Determination Theory was applied as the theoretical framework. A sample of 135 women aged between 40 and 88 years (59.66 ± 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
4
7
1
4
Order By: Relevance
“…The authors [34], in a meta-analysis with most of the non-experimental studies, determined that there is a strong relationship between the self-determination theory [17] and positive health behaviours. Analogous observations were obtained in several studies [14,[18][19][20]35].…”
Section: Discussionsupporting
confidence: 89%
“…The authors [34], in a meta-analysis with most of the non-experimental studies, determined that there is a strong relationship between the self-determination theory [17] and positive health behaviours. Analogous observations were obtained in several studies [14,[18][19][20]35].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the results obtained for external regulation and amotivation were in contrast to the hypotheses proposed for this research. Furthermore, these findings also contrasted with previous studies [43], given that they found a significant decline in adults' levels of external regulation and amotivation after an exercise program. It is likely that the low levels of external regulation and amotivation found at the beginning of the intervention program should be considered, which makes us think that, although there were changes on both motivational forms, these did not reach the level of statistical significance.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from this study showed statistically significant increases for the parents' level of integrated and identified regulation, consistent with one of the hypotheses raised in this study. Moreover, these findings are shown, to some extent, to be in consonance with previous works that revealed an increase in identified regulation in adults after an exercise program [43]. Furthermore, the results are aligned with the findings obtained by Ntoumanis et al [26], Rodrigues et al [28] and Teixeira et al [27], who pointed out that while identified regulation represented the motivational form that exerted the highest influence on initial/short-term PA adherence, integrated regulation was a strong predictor of long-term PA in adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, extrinsic motivation relates to factors external to the subjectsuch as the environment, coaches and parents -which allow specific results through behaviour driven by pressure or external rewards [9]. Extrinsic motivation shows itself related to social aspects, appearance, and fitness [12,13]. in this context, motivation provides an understanding of the reasons why children and adolescents practise soccer, since it makes possible to gain knowledge about the reasons that initiate, regulate, sustain, direct, and interrupt the behaviour during the experience in this sport [7,8,14].…”
Section: Introductionmentioning
confidence: 99%